ANTISIPASI KEDATANGAN KENDARAAN DARURAT MELALUI EMERGENCY MESSAGE PADA LINGKUNGAN VEHICULAR ADHOC NETWORK - Johan Ericka W.P (STMIK YADIKA BANGIL, 2017)
VANET (Vehicular Ad Hoc Network) is a relatively new technology in computer network.This technology will enable communication between vehicles by sending datas wirelessly. This research will use VANET technology to broadcast emergency messages, so every vehicles that receive the emergency data can do anticipating action (stop / pull over / slowdown) to clear the road for emergency vehicles (police / firetrucks / ambulance). Keywords: VANET, emergency message, anticipating